Clinical and morphological changes in the liver in patients with pulmonary tuberculosis - Ergashov Behruzjon Komilovich (Journal of Innovation in Education and Social Research, 2025)
The aim of this study is to obtain information about the clinical and morphological changes in the liver in patients with pulmonary tuberculosis.